Disentangling Associations Between Frequency of Specifific Social Networking Site Platform Use, Normative Discrepancies, and Alcohol Use Among Adolescents and Underage Young Adults - Dana M. Litt; Angeles Astorga; Kayla Tate; Erika L. Thompson; Melissa A. Lewis (New Prairie Press, 2021)
Although there is a robust literature examining normative discrepancies for drinking, less is known related to normative discrepancies related to alcohol-posting behavior on social networking sites (SNS). Given that SNS are posited to be an important risk factor for adolescent and young adult alcohol use, the aims of the present study were to: (1) document descriptive and injunctive normative discrepancies for number of alcohol-related posts on SNS, (2) examine associations between frequency of using SNS platforms (Facebook, Instagram, Snapchat) and descriptive and injunctive normative discrepancies, and (3) to examine whether descriptive and injunctive normative discrepancies are associated with willingness to use alcohol and drinking among adolescents and young adults. Data were drawn from the baseline assessment of a larger longitudinal experimental study (N= 306, age 15-20). Overall, participants perceived that their peers are more approving of and post about alcohol use more often than they do themselves, thus indicating significant descriptive and injunctive normative discrepancies. More frequent use of Facebook was associated with having greater descriptive normative discrepancies, whereas frequency of both Facebook and Instagram use were associated with greater injunctive normative discrepancies. Results further indicated that controlling for frequency of SNS use, descriptive normative discrepancies, but not injunctive, were associated with greater willingness to drink and drinks per week. Results provide evidence that in particular, descriptive normative discrepancies for SNS use may be important to target when planning intervention programs to reduce the impact of SNS use on adolescent and young adult alcohol use.